Mechanical thrombectomy performs similarly in real world practice: a 2016 nationwide study from the Czech Republic. (16th November 2017) - Volny, Ondrej; Krajina, Antonin; Belaskova, Silvie; Bar, Michal; Cimflova, Petra; Herzig, Roman; Sanak, Daniel; Tomek, Ales; Köcher, Martin; Rocek, Miloslav; Padr, Radek; Cihlar, Filip; et al.
Abstract : Background: Randomized clinical trials have proven mechanical thrombectomy (MT) to be a highly effective and safe treatment in acute stroke. The purpose of this study was to compare neurothrombectomy data from the Czech Republic (CR) with data from the HERMES meta-analysis. Methods: Available nationwide data for the CR from 2016 from the Safe Implementation of Treatments in Stroke–Thrombectomy (SITS-TBY) registry for patients with terminal internal carotid artery (ICA) and/or middle cerebral artery (MCA) occlusions were compared with data from HERMES. CR and HERMES patients were comparable in age, sex, and baseline National Institutes of Health Stroke Scale scores. Results: From a total of 1053 MTs performed in the CR, 845 (80%) were reported in the SITS-TBY. From these, 604 (72%) were included in this study. Occlusion locations were as follows (CR vs HERMES): ICA 22% versus 21% (P=0.16), M1 MCA 62% versus 69% (P=0.004), and M2 MCA 16% versus 8% (P<0.0001). Intravenous thrombolysis was given to 76% versus 83% of patients, respectively (P=0.003). Median onset to reperfusion times were comparable: 232 versus 285 min, respectively (P=0.66). A modified Thrombolysis in Cerebral Infarction score of 2b/3 was achieved in 74% (433/584) versus 71% (390/549) of patients, respectively (OR 1.17, 95% CI 0.90–1.5, P=0.24). There was no statistically significant difference in the percentage of parenchymalhematoma type 2 (OR 1.12, 95% CI 0.66–1.90, P=0.68). A modified Rankin Scale score of 0–2 at 3 months was achieved in 48% (184/268) versus 46% (291/633) of patients, respectively (OR 0.92, 95% CI 0.71–1.18, P=0.48). Conclusions: Data on efficacy, safety, and logistics of MT from the CR were similar to data from the HERMES collaboration.